ANALISIS RISIKO KECELAKAAN KERJA DENGAN METODE RULA DAN OWAS PADA INDUSTRI TAHU - Suryaningrat, Ida Bagus; Wibowo, Yuli; Sari, Bella Yusita (BPFP Faperta UNIB, 2023)
The stembel tofu industry is a micro business located in Stembel Village, Gambiran District, Banyuwangi Regency. The industry was founded in 2000 until now. The workforce in this tofu industry is 10 workers. In the tofu industry, it employed enough labor starting from the production process to distribution which means as a service provider. Tofu shaping activities were carried out by workers manually using human power. Activities that were carried out continuously can cause the risk of musculoskeletal disorders in workers. The used of the Nordic Body Map questionnaire identified workers experiences in the process of tofu making process. The OWAS and RULA methods were implemented to evaluate and analyze worker activities that caused injuries to musculoskeletal disorders. Some of the activities in the tofu shaping process included the flattening of the fabric sheet, the stage of taking lumps of tofu, pressing, reversing I and II, transferring the printed product to cutting, and cutting the tofu. From the seven activities, the results of calculating the OWAS and RULA methods were high risk at the stage of collecting tofu lumps, pressing, and cutting tofu with an OWAS score obtained a level 4 score and a RULA risk level score of 4. The analysis results showed that some worker postures caused musculoskeletal risk so that need to be repaired. The suggestion for improving work posture was to design a tool in the form of a tofu lump retrieval tool and a tofu mold tool to reduce risk of musculoskeletal injuries to the workers.